Functional Roles of microRNAs in Agronomically Important Plants—Potential as Targets for Crop Improvement and Protection - Djami-Tchatchou, Arnaud T.; Sanan-Mishra, Neeti; Ntushelo, Khayalethu; Dubery, Ian A. (Frontiers in Plant Science, 2017)
MicroRNAs (miRNAs) are a class of small non-coding RNAs that have recently emerged as important regulators of gene expression, mainly through cleavage and/or translation inhibition of the target mRNAs during or after transcription. miRNAs play important roles by regulating a multitude of biological processes in plants which include maintenance of genome integrity, development, metabolism, and adaptive responses towards environmental stresses. The increasing population of the world and their food demands requires focused efforts for the improvement of crop plants to ensure sustainable food production. Manipulation of mRNA transcript abundance via miRNA control provides a unique strategy for modulating differential plant gene expression and miRNAs are thus emerging as the next generation targets for genetic engineering for improvement of the agronomic properties of crops. However, a deeper understanding of its potential and the mechanisms involved will facilitate the design of suitable strategies to obtain the desirable traits with minimum trade-offs in the modified crops. In this regard, this review highlights the diverse roles of conserved and newly identified miRNAs in various food and industrial crops and recent advances made in the uses of miRNAs to improve plants of agronomically importance so as to significantly enhance crop yields and increase tolerance to various environmental stress agents of biotic - or abiotic origin.